Performatividade e espaço público : processos comunicacionais no teatro de rua - Fonseca, Michelle Nascimento Cabral (2016)
The present research aims to investigate the street theater communication process, having the city as a space of connections between these two universes: communication and theater. It is interesting to understand, specifically, the way the street plays are seen, understood and redefined by the street audience, in the act of their reception in the contemporary public space. Understanding the theatrical intervention of the street as an act of complex communication, which involves different social fields, we preferred, in our subject, the communicational processes developed in its practice, emphasizing the relation of this theater with the audience and the contemporary public space. We understand that this unusual encounter of the theater with the individual, inhabitant or transient in that place, is a singular moment, what enables aesthetic discourse, when appropriating the public space, to trigger an intense dialogic process, providing a moment of multiple interactions. For this reason, this research focus on cultural studies, the ideal field to think about communication and its subjects, outside the dichotomic visions and plastered to a universe of connections, displacements and interpretations. Thus, a cut in the vast universe of theater groups that adopt the public space as a place of aesthetic manifestation will be done. Therefore, the present research will analyze the theatrical production of two specific groups, the Cooperativa de Artistas Teatrais Oigalê / RS in the spectacles Deus e o Diabo em terra de Miséria and O baile dos Anastácio and, the Teatro de Operações/ RJ group in the spectacles A cena é pública and BTGBT 14059 câmbio. Having these spectacles as an object we undertake our analysis of the communicational processes in the street theater in its relationship with the spectator, the public space and the interactions generated from these experiences. This research allows us to understand the networks woven in this symbolic place, which is the enjoyment of theatrical art in relation to the concrete organism of the city. This connection leads us to realize that effective transformations take place in cultural and aesthetic appropriation, through a communication process, which subverts the linear and simplified order of "emission - message - reception" proposing a set of transitions and superpositions, which provokes the Empowerment of the recipient subject, and that, in this process, one finds the sense of citizenship.